Investigation of Fractional Partial Differential Equations in the College Course Mathematical Physics Equations - Feng, Qinghua (IJRDO- Journal of Educational Research, 2018)
We introduce a new approach for solving fractional partial differential equations, where the fractional derivative is defined in the sense of the conformable fractional derivative. As for applications of this approach, we apply it to seek exact solutions for the space-time fractional BBM equation successfully .